Pengaruh Pemupukan Nitrogen Terhadap Laju Fotosintesis, Kandungan Klorofil, Dan Pertumbuhan Tanaman Jagung (Zea Mays L.) - Yanuari Hulu; Helmin Parida Zebua; Dencervis Gulo; Wendi Warisman Harefa; Sastra Alberta Hia; Serlin Jessica Mendrofa (CV. SINAR HOWUHOWU, 2026)
Nitrogen is an essential nutrient that plays an important role in chlorophyll formation and photosynthesis. This study aimed to determine the effect of nitrogen fertilization on photosynthesis rate, chlorophyll content, and growth of maize (Zea mays L.). The research was conducted from October to December 2025 in Dahana Village, Universitas Nias, using a Completely Randomized Design (CRD) with four nitrogen levels and five replications. Observed parameters included plant height, number of leaves, and plant dry weight. Data were analyzed using analysis of variance (ANOVA) and LSD test at the 5% level. The results showed that nitrogen fertilization significantly affected maize growth by increasing plant height, leaf number, and dry weight. However, excessive nitrogen application did not always result in optimal growth. Therefore, appropriate nitrogen fertilization is required to support optimal maize growth.